THE LAST DAYS OF MEGALI IDEA IN IZMIR: FROM 30 AUGUST TO 15 SEPTEMBER THE ASIA MINOR DISASTER - Gürhan YELLİCE (Fırat University, 2019)
The Turkish-Greek War of 1919-1922 became one of the most important turning points in the history of both nations. This important historical event, for the Turks who had won the war, created a new beginning of the establishment of a new state from the ashes of a destroyed Empire. The date of August 30, 1922 symbolizes the day that the Turkish-Greek War of 1919-1922 was won and the date of September 9, 1922 the liberation and independence of the Turkish Nation. On the other hand these dates, from the Greek point of view, mark the catastrophic end of the Anatolian Adventure and the Megali Idea project, which was an imaginary project for many years. Although there are many studies in the national and international literature regarding these dates and the Greek-Turkish War, there is no systematic account that thoroughly examines and evaluates the impact of the defeat on Greek politics and public opinion, especially on the reflections of the Greek press. Focusing on the dates between Augoust 30-15 Semtember 1922, the aim of this work is to examine how “the defeat”, which was considered as "Asia Minor Catastrophe" in Greek history, was evaluated in the Greek Press of the period. The Greek newspapers will be evaluated by dividing into three groups: The Royalist, The Venizelist and the Communist Rizospastis. In the Royalist Press Embros and Skrip, and in the Venizelist Press Patris ve Makedonia will generally be analyzed.